2010
DOI: 10.1007/s00244-010-9611-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood, Urine, and Sweat (BUS) Study: Monitoring and Elimination of Bioaccumulated Toxic Elements

Abstract: There is limited understanding of the toxicokinetics of bioaccumulated toxic elements and their methods of excretion from the human body. This study was designed to assess the concentration of various toxic elements in three body fluids: blood, urine and sweat. Blood, urine, and sweat were collected from 20 individuals (10 healthy participants and 10 participants with various health problems) and analyzed for approximately 120 various compounds, including toxic elements. Toxic elements were found to differing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 58 publications
3
81
1
Order By: Relevance
“…Data for this investigation are derived from the Blood, Urine, and Sweat (BUS) study. Other findings from this study have been published elsewhere [2730]. …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Data for this investigation are derived from the Blood, Urine, and Sweat (BUS) study. Other findings from this study have been published elsewhere [2730]. …”
Section: Introductionsupporting
confidence: 61%
“…The BUS study as a whole tested for 120 chemical agents and found exposure to varying degrees in each participant [27]. Accordingly, it is not possible to attribute contamination from a single agent to a particular clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that many toxins appeared to be present preferentially in sweat and not in serum, thereby confirming that sweat appeared to be a potential conduit for the elimination of some toxins [39]. Later, some researchers used methods such as saunas to induce sweating and ascertain whether they could help excrete toxins such as lead, thiuram, captax, sulphenamide C, methamphetamine and related chemical compounds that invaded the body during everyday work activities.…”
Section: Metabolic and Excretory Functions Of Sweatmentioning
confidence: 93%
“…276 An important finding of the study was that excretion of certain toxic elements occurs preferentially via sweat. A set of 18 elements was analysed in blood spots from new-born children.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 98%